Computed tomographic attributes in asthma-chronic obstructive pulmonary disease overlap - Azza Farag Said; Arwa Mohamed Rady; Hosny Sayed Abdel Ghani; Rasha A. Abdelfattah; Yosra M. Mousa; Bahaa Ibrahim Mohamed (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Limited number of studies analyzed imaging features in patients with asthma-COPD overlap (ACO). In patients with ACO, we evaluated their qualitative and quantitative CT imaging characteristics. Patients and methods Thirty-five ACO patients (15 men and 20 women) with a mean age of 58.6 yrs. and thirty COPD patients made up the study population. Fifteen healthy volunteers who were the same age and sex as the study population were chosen to serve as a control group. Patient demographics, pulmonary symptoms, spirometry, COPD grading, and disease severity were evaluated. CT scans of the whole inspiration and expiration phases were examined visually for signs of emphysema, air trapping, and bronchial wall thickening. Emphysema as low-attenuation area (LAA% < −950), wall area percentage (WA%) and air trapping as the expiration-to-inspiration ratio of the mean lung density (MLDE/I)%) were all evaluated using quantitative CT analysis software. Results Visual examination of the CT data showed very identical findings in both patient groups, except for a noticeably larger main pulmonary artery diameter in COPD patients when compared to ACO patients and healthy controls. Quantitative CT analysis depicted that patients with ACO and COPD had higher LAA% and WA% than controls. ACO patients had a much lower LAA% than COPD patients, while they had a significantly greater WA% than COPD patient. Despite being higher in ACO patients than COPD patients, air trapping was not statistically significant. Conclusion Visual CT was unable to identify most radiological changes between patients with ACO and those with COPD. Compared to individuals with COPD, people with ACO exhibit more airway alterations but a lower degree of emphysema on quantitative CT analysis.